Ritatoon Learning Media Assisted by QR Code to Increase Student Learning Interest in Grade V Elementary School Science Content - Made Yuni Supartini; Made Padmarani Sudewiputri; Ketut Susiani (Jurnal Media dan Teknologi Pendidikan, 2025)
Science and social studies learning in elementary schools should foster students’ curiosity, learning interest, and active engagement through the use of creative, interactive, and contextually relevant learning media. However, in reality, classroom practices are still dominated by conventional, teacher-centered methods with limited media innovation, leading to students’ low motivation and passive participation. Addressing this gap, the present study aims to develop and examine the effectiveness of Ritatoon, a QR-Code-assisted learning media, in enhancing students’ learning interest in the topic My Beloved Region. This research employed a research and development (R&D) approach using the ADDIE model and a one group pretest-posttest design. The participants were fifth-grade elementary students. Data were collected through expert validation questionnaires, practicality surveys, and learning achievement tests, and analyzed using both qualitative and quantitative descriptive methods. The findings revealed that Ritatoon achieved a very high level of validity and practicality, and significantly improved students’ learning interest and outcomes. The implication suggests that technology-based innovative media such as Ritatoon with QR-Code integration can serve as an effective strategy to overcome low student motivation and participation while reinforcing active and contextual learning in elementary education.